Cortico-striatal spike-timing dependent plasticity after activation of subcortical pathways - Schulz, Jan M.; Redgrave, Peter; Reynolds, John N. (Frontiers in Synaptic Neuroscience, 2010)
Cortico-striatal spike-timing dependent plasticity (STDP) is modulated by dopamine in vitro. The present study investigated STDP in vivo using alternative procedures for modulating dopaminergic inputs. Postsynaptic potentials (PSP) were evoked in intracellularly recorded spiny neurons by electrical stimulation of the contralateral motor cortex. PSPs often consisted of up to three distinct components, likely representing distinct cortico-striatal pathways. After baseline recording, bicuculline (BIC) was ejected into the superior colliculus (SC) to disinhibit visual pathways to the dopamine cells and striatum. Repetitive cortical stimulation (~60; 0.2 Hz) was then paired with postsynaptic spike discharge induced by an intracellular current pulse, with each pairing followed 250 ms later by a light flash to the contralateral eye (n=13). Changes in PSPs, measured as the maximal slope normalised to 5 min pre, ranged from potentiation (~120%) to depression (~80%). The determining factor was the relative timing between PSP components and spike: PSP components coinciding or closely following the spike tended towards potentiation, whereas PSP components preceding the spike were depressed. Importantly, STDP was only seen in experiments with successful BIC-mediated disinhibition (n=10). Cortico-striatal high-frequency stimulation (50 pulses at 100 Hz) followed 100 ms later by a light flash did not induce more robust synaptic plasticity (n=9). However, an elevated post-light spike rate correlated with depression across plasticity protocols (R2=0.55, p=0.009, n=11 active neurons). These results confirm that the direction of cortico-striatal plasticity is determined by the timing of pre- and postsynaptic activity and that synaptic modification is dependent on the activation of additional subcortical inputs.